Litigating Economic, Social and Cultural Rights against Transnational Corporations in Indonesian Court - Iman Prihandono (Faculty of Law, Hasanuddin University, 2017)
States should take appropriate steps to ensure the effectiveness of domestic judicial mechanisms when addressing business-related human rights abuses. These steps may include ways to reduce legal, practical and other relevant barriers that could lead to a denial of access to remedy. To a certain degree, these problems exist in Indonesia’s judicial remedy mechanism. This article examines court decisions in five cases involving Transnational Corporations (TNCs). These decisions are examined to identify challenges and opportunities in bringing a case on ESC rights violations against TNCs. It is found that claim on ESC rights violation may be brought to the court, and the court has jurisdiction to entertain the case. However, of the five cases filed against TNCs, only in one case has the court decided in favour of the plaintiff. Most of the cases were rejected on procedural matters. This situation suggests that it remains burdensome for the victims of ESC rights violations to seek remedy at the court. There are procedural burdens that has to be faced by plaintiff when bringing ESC rights case against corporations, particularly TNCs. Nevertheless, there are new develop-ments in relation with pursuing ESC rights in court. One of the important development is private business contract between the govern-ment and private corporations may be annulled by the court, if the exercise of the contract would violate the government's obligation to fulfil human rights of the citizens